Developing a Model for the Establishment of Pre-Hospital Emergency Medicine Bases in the Northern Provinces of Iran - Ahmadi Dashtiyan, Azadeh; Masoudi Asl, Iravan; Riahi, Leila; Mahmoodi, Mahmood (Farmeconomia. Health Economics and Therapeutic Pathways, 2019)
BACKGROUND: The faster and more accurately Pre-Hospital Emergency Medicine as the first line of care and treatment is done, the less the mortality and disability rates are. AIM: The present study is an attempt to design a model for the establishment of pre-hospital emergency bases in the northern provinces of Iran. METHODS: This quantitative-qualitative (mixed-method) research was conducted in two parts: First, using the literature review, interviews with experts in the field, and a comparative study, the most important factors affecting the establishment were extracted. Second, the obtained data were employed to formulate the development model and to design the questionnaire. The required data for factor analysis were collected through a questionnaire distributed among 200 operational personnel in January 2018. The results were analyzed using confirmatory factor analysis and multiple regression. RESULTS: Five components were identified after the exploratory factor analysis and Varimax with an eigenvalue larger than 1. The effect coefficients calculated for human resources components, service speed, and information and communication system were 0.935, 0.765 and 0.752, respectively. The obtained goodness of fit was very close to one, indicating the one-dimensional strength of the model. The highest parameter estimation in this model was allocated to the human component as 0.935, which has a significant correlation with other components. CONCLUSIONS: In order to reduce the response time, more attention should be paid to the allocation of budget and organizational roles, education, participation from government departments, establishment of an independent medical emergency organization, and appropriate accessibility to reduce the rates of mortality and morbidity.